Фізико-хімічні та медико-біологічні дослідження системи нанокремнезем ? рутин ? катіонна ПАР - Fedianina, T. V.; Barvinchenko, V. N.; Lipkovska, N. A.; Rugal, A. A.; Chepel, L. I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
Physicochemical studies of the system nanosilica?routin?cationic surfactant bensildimethyl [3-(miristoilamino)propyl] ammonium chloride have shown that spectral and protolytic properties, solubility, and adsorption of routine depend on the concentration of cationic surfactant in solution and crucially change when exceeding the critical micelle concentration. On the basis of research results ternary dental medication containing nanosilica and routin in the form of a supramolecular complex with bensildimethyl [3-(miristoilamino)propyl] ammonium chloride , which is antiseptic of multipurpose action, was developed for the treatment of periodontal diseases. Clinical trials have shown high efficiency of these medications.